2021
DOI: 10.1097/md.0000000000024267
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced recovery after surgery for laparoscopic gastrectomy in gastric cancer

Abstract: Background: Laparoscopic distal gastrectomy (LDG) has been highlighted for its safety and better short-term clinical outcomes in treating gastric cancer. However, only a slight reduction of the post-operative hospital stay was observed in gastric cancer patients undergoing LDG with conventional perioperative management, compared to patients undergoing open surgery. Thus, an enhanced recovery after surgery (ERAS) program for LDG is needed to further reduce the post-operative hospital stays. This pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…[18] Meanwhile, the intestinal paralysis of patients after gastrointestinal tumor resection is often dynamic rather than mechanical, so the gastrointestinal mucosa can absorb digestive juices normally, and chewing gum can induce the release of various gastrointestinal hormones and increase the secretion of saliva and pancreatic juice through vagus nerve stimulation, which can maintain the normal absorption function of the gastrointestinal tract. [19] Patients use only masticatory muscles during chewing gum, without swallowing food, which does not lead to related complications. [20] It has been suggested that chewing gum constituents (hexitol) play an important role in improving postoperative gastrointestinal paralysis.…”
Section: Discussionmentioning
confidence: 99%
“…[18] Meanwhile, the intestinal paralysis of patients after gastrointestinal tumor resection is often dynamic rather than mechanical, so the gastrointestinal mucosa can absorb digestive juices normally, and chewing gum can induce the release of various gastrointestinal hormones and increase the secretion of saliva and pancreatic juice through vagus nerve stimulation, which can maintain the normal absorption function of the gastrointestinal tract. [19] Patients use only masticatory muscles during chewing gum, without swallowing food, which does not lead to related complications. [20] It has been suggested that chewing gum constituents (hexitol) play an important role in improving postoperative gastrointestinal paralysis.…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical practice of ERAS, the unnecessary use of analgesics is avoided. In a phase 3 study in which Aoyama et al compared open vs. minimal invasive surgery, they reported that the extra use of acetaminophen was significantly higher in the open surgery group compared to the minimal invasive surgery group (18.3% vs. 6.2%, p: 0.03) [ 12 ].Today, combining minimal invasive surgery with ERAS is associated with lesser pain, an accelerated healing process, and an early return of gastrointestinal functions compared to conventional open surgery [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ].Fumagalli et al practiced minimally invasive surgery to 28% of 270 cases [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jeonget al reported that most patients could resume an oral diet within 1 or 2 days with conservative care, and no serious complication occurred that was associated with early oral nutrition, such as aspiration or anastomosis leakage [ 13 ].Jie Ding et al reported that in meta-analysis studies, a reduction in time to first flatus is an important part of ERAS [ 16 ].Rohck et al achieved their goal of early oral feeding and discharge on the 4th day after surgery in 127 patients with stage 1 and 2a gastric cancer, with a rate of 77% [ 17 ]. Li et al determined that ERAS did not prolong the time to first flatus and did not increase complication rate in their eight RCT and meta-analysis series consisting of 400 cases [ 18 ].Liayang et al reported in their prospective study consisting of 98 cases that oral clear water on post-operative day 1 was accommodated by 86% of patients, oral liquid diet on post-operative day 2 was accommodated by 70% of patients, and oral semi fluid diet on post-operative day 3 was accommodated by 60% of patients [ 6 ]. In our study, we found that starting early oral intake in the ERAS group did not increase the risk of leakage, and the time to first flatus was earlier than the non-ERAS group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the Editor We have read with interest the article published by Blumenthaler et al 1 Many studies have confirmed that enhanced recovery after surgery (ERAS) can promote the postoperative rehabilitation of patients with gastric cancer, shorten the length of stay and reduce the cost of hospitalization. [2][3][4] It is precisely because of its good social and economic benefits that it has become the focus of global research.…”
Section: Perioperative-enhanced Recovery Protocol In Patients Undergoing Open Gastrectomy For Gastric Cancermentioning
confidence: 99%